1993
DOI: 10.1007/bf01715054
|View full text |Cite
|
Sign up to set email alerts
|

High PAI activity with correlation to triglyceride and HDL cholesterol values in patients with coronary artery disease with no difference in survivors of myocardial infarction

Abstract: The fibrinolytic capacity of blood depends mainly on the amount of tissue-type plasminogen activator (t-PA) activity and plasminogen activator inhibitor type-1 (PAI-1) activity. Previous studies linked high PAI activity or low t-PA activity with the development of atherosclerosis and thromboembolic diseases. Yet, there are conflicting reports in the literature as to whether there is higher PAI activity in patients with myocardial infarction (MI) than in patients with coronary artery disease (CAD) without previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The efficacy of PAI-1 in preventing thrombolysis was recently tested in animal models. The reactivated PAI-1 could rapidly reverse the bleeding tendency induced by the combination of rt-PA and aspirin in rabbits (31) and effectively prevented thrombolysis in vivo (32). Hence, it was suggested that PAI-1 may be used as an antidote to treat hemorrhagic complications brought about by the administration of thrombolytic agents (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of PAI-1 in preventing thrombolysis was recently tested in animal models. The reactivated PAI-1 could rapidly reverse the bleeding tendency induced by the combination of rt-PA and aspirin in rabbits (31) and effectively prevented thrombolysis in vivo (32). Hence, it was suggested that PAI-1 may be used as an antidote to treat hemorrhagic complications brought about by the administration of thrombolytic agents (32).…”
Section: Discussionmentioning
confidence: 99%
“…The reactivated PAI-1 could rapidly reverse the bleeding tendency induced by the combination of rt-PA and aspirin in rabbits (31) and effectively prevented thrombolysis in vivo (32). Hence, it was suggested that PAI-1 may be used as an antidote to treat hemorrhagic complications brought about by the administration of thrombolytic agents (32). On the other hand, neutralization of plasma PAI-1 by monoclonal antibody (13) or low molecular weight inhibitors (14) increased fibrinolysis and protected against thrombus formation in animals.…”
Section: Discussionmentioning
confidence: 99%
“…PLG is plasminogen and closely linked to tissue plasminogen activator (tPA) and plasminogen activator inhibitor-1 (PAI-1) in this pathway. In the previous report, PAI-1 is negatively correlated with plasma HDL-cholesterol levels [25]. Thus plasminogen up-regulation may lead to higher plasma levels of HDL-cholesterol.…”
Section: Discussionmentioning
confidence: 66%